Source mechanism studies on Witwatersrand seismic events - Spottiswoode, Stephen Morrison (My University, 1980)
The physical processes at the source of mine tremors at the East Rand Proprietary Mines (E.R.P.M.) near Johannesburg were investigated. [Abbreviated Abstract. Open document to view full version]
Thesis (Ph.D.)--University of the Witwatersrand, Science Faculty (Geophysics), 1980
Keywords: Seismology--Research--South Africa--Transvaal